Implementasi Etika Budaya Sekolah 3S (Senyum Sapa Salam) Terhadap Siswa di SDN 66 Kota Bengkulu - Kurnida, Yessi Nur Esa; Tri Deta Febriyanti; Padhilah; Eka Puspa Dewi (JPT : Jurnal Pendidikan Tematik, 2025)
School culture plays an important role in shaping students' character and ethics from an early age. One form of positive culture implemented in elementary schools is the 3S culture (Smile, Greeting, Greeting) which aims to foster polite, friendly, and respectful attitudes towards others. This study aims to describe the implementation of the 3S school culture ethics towards students at SDN 66 Bengkulu City and its influence on students' social behavior in the school environment. This study uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The research informants consisted of the principal, teachers, and students in grades IV to VI. Data were analyzed using the Miles and Huberman interactive model, including data reduction, data presentation, and drawing conclusions. The results of the study indicate that the 3S culture has been implemented consistently by teachers and school staff, and has had a positive impact on the formation of student character, such as increasing respect, politeness, and the ability to interact socially. However, several challenges were still found in terms of the consistency of implementation and participation of certain students. It can be concluded that the implementation of the 3S school culture ethics at SDN 66 Bengkulu City plays an important role in building a friendly and characterful school environment. This culture is worthy of being used as a strategy for sustainable character building in elementary schools.